2001
DOI: 10.1126/science.1058582
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Origins for Recent North Atlantic Climate Change

Abstract: result in measurable but modest changes in N concentration over short distances in some streams, whereas much larger changes are associated with disturbance of the adjacent landscape by humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
362
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 575 publications
(395 citation statements)
references
References 27 publications
26
362
2
5
Order By: Relevance
“…Chiang et al (2002) found that the local meridional SST gradient is one of the dominant factors in controlling boreal spring Atlantic Intertropical Convergence Zone variability. Hoerling et al (2001) demonstrated that the progressive warming of the equatorial oceans is associated with climate changes over the North Atlantic, and warmer tropical SSTs force a positive North Atlantic Oscillation phase; and this was further confirmed by Magnusdottir et al (2004). Brierley and Fedorov (2010) revealed that the impacts over North America of changes in the meridional SST gradient are somewhat stronger than those from zonal SST variations.…”
Section: Introductionsupporting
confidence: 51%
“…Chiang et al (2002) found that the local meridional SST gradient is one of the dominant factors in controlling boreal spring Atlantic Intertropical Convergence Zone variability. Hoerling et al (2001) demonstrated that the progressive warming of the equatorial oceans is associated with climate changes over the North Atlantic, and warmer tropical SSTs force a positive North Atlantic Oscillation phase; and this was further confirmed by Magnusdottir et al (2004). Brierley and Fedorov (2010) revealed that the impacts over North America of changes in the meridional SST gradient are somewhat stronger than those from zonal SST variations.…”
Section: Introductionsupporting
confidence: 51%
“…Это означает, что влияние ано-малий ТПО передается через одну и ту же атмосферную циркуляционную моду, влияющую на океанический перенос тепла в Северной Атлантике. Такой циркуляционной модой может быть Северо-Атлантическое колебание (САК), изменяющееся под влиянием аномалий ТПО в Атлантическом, Индий-ском и Тихом океанах (Нестеров, 2013;Robertson et al, 2000;Hoerling et al, 2001;Sutton, Hodson, 2002;и др.). В настоящей статье это подтверждается корреляционным анализом связи между аномалиями ТПО и индексами Северо-Атлантического колебания, который показал отрицательную корреля-цию между ними для всех трех океанов.…”
Section: -аномалия тпо 2 -гольфстрим 3 -северо-атлантическое течениunclassified
“…Отмечено, что в результатах экспериментов с глобальными моделями климата из CMIP5 с антропогенным форсингом не найдено аналогичных изменений в циркуляции и потеплении. В работе (Hoerling et al, 2001) была отмечена отрицательная связь между аномалиями ТПО в низких широтах океана и индексом САК, а так-же отрицательная корреляция между САК и ТПО в Северной Атлантике выше 40° с.ш.. Такое соответствие между САК и ТПО особенно ярко про-является при экстремально низком и высоким среднегодовых значениях САК. На рис.…”
Section: -аномалия тпо 2 -гольфстрим 3 -северо-атлантическое течениunclassified
See 1 more Smart Citation
“…During the winter, the plateau is particularly influenced by the Siberian High, which is closely related to the NAO and NPO (North Pacific Oscillation) [54][55][56]. Two additional global-scale climate systems play extremely important roles in the climate and environment of the Mongolian Plateau.…”
Section: Regional Comparison and Teleconnectionsmentioning
confidence: 99%